Interband Lag Variability in Active Galactic Nuclei across Zwicky Transient Facility Data from Multiple Years - Zhen-Bo Su; Zhen-Yi Cai; Hengxiao Guo; Mouyuan Sun; Jun-Xian Wang (The Astrophysical Journal)
Interband lags in the optical continua of active galactic nuclei (AGNs) have been observed over years of monitoring, yet their physical origins remain unclear. While variable interband lags have potentially been found in a few individual AGNs, the temporal behavior of the interband lags of an AGN sample has not been explored systematically. Here, we analyze the interband lags of 94 bright AGNs at z < 0.8, using both seasonal 1 yr and full 6 yr gri -band light curves from Zwicky Transient Facility Data Release 22. We find that more than half of the 94 AGNs show significant seasonal variations in the interband lags. Besides, the short-term lags, derived by averaging the lags inferred from multiple seasonal light curves, are consistently smaller than the long-term lags, which are inferred from the full 6 yr light curves. This supports recent theoretical simulations where the lag measurement is sensitive to the baseline of the light curve and the lag variation could be simply attributed to the inherent randomness of AGN variability. Our findings suggest that the interband lags of AGNs are more complex and stochastic than commonly thought, and highlight the importance of high-precision time-domain surveys for uncovering the properties of AGN variability as well as the associated accretion physics.